Antihypertensive therapy to prevent cardiac death: A study of combined ACE inhibitors and β-blockers—a retrospective cohort study in Tsunan Town, Japan - Shinichiro Ishikawa; Yusaku Hayashi; Toshiyuki Abe; Susumu Tanaka (PLoS ONE, 2025)
Antihypertensive treatment is widely known to reduce the risk of cardiovascular mortality; however, its protective effect, specifically against cardiac death, remains unclear. In this study, we examined whether a treatment strategy prioritizing the combined use of angiotensin-converting enzyme inhibitors and β-blockers reduces the risk of cardiac death in outpatient hypertensive patients. This retrospective observational cohort study was conducted at a single facility over a 30-year period, using data obtained between 1987 and 2016. Between 1992 and 2001, a combined treatment approach using angiotensin-converting enzyme inhibitors and β-blockers was preferentially used to suppress neurohumoral factors, with calcium channel blockers and diuretics used as supplementary medications. Standardized mortality ratios for all-cause mortality, cardiac death, and cerebrovascular death during each period were tracked and compared with nationwide data in Japan. Since 1992, the standardized mortality ratios for all-cause mortality and cardiac death in Tsunan Town have significantly decreased and fallen below the national averages. The present study focused on the role of neurohumoral factors, and we observationally evaluated the impact of combined therapy with angiotensin-converting enzyme inhibitors and β-blockers on the prognosis of patients with hypertension. While providing a perspective that has not been sufficiently examined to date, our findings should be regarded as the generation of an important hypothesis that warrants confirmation through future rigorous interventional studies.